Coordination and activation of nitrous oxide by iron zeolites - Bols, Max L.; Snyder, Benjamin E. R.; Rhoda, Hannah M.; Cnudde, Pieter; Fayad, Ghinwa; Schoonheydt, Robert A.; Van Speybroeck, Veronique; Solomon, Edward I.; Sels, Bert F. (Nature catalysis, 2021)
Iron-containing zeolites are heterogeneous catalysts that exhibit remarkable activity in the selective oxidation of inert hydrocarbons and catalytic decomposition of nitrous oxide (N 2 O). The reduction of N 2 O is critical to both these functions, but experimental data tracking the iron active sites during N 2 O binding and activation are limited. Here, the N 2 O-ligated Fe( ii ) active site in iron-exchanged zeolite beta is isolated and characterized by variable-temperature Mössbauer, diffuse reflectance UV-vis-NIR and Fourier transform infrared spectroscopy. N 2 O binds through the terminal nitrogen atom with substantial backbonding from the Fe( ii ) centre at low temperature. At higher temperatures, the Fe–N 2 O interaction is weakened, facilitating isomerization to the O-bound form, which is competent in O-atom transfer. Density functional theory calculations show the geometric and electronic structure requirements for N 2 O binding and activation. A geometric distortion imposed by the zeolite lattice plays an important role in activating N 2 O. This highlights a mechanism for structural control over function in Fe-zeolite catalysts. Nitrous-oxide-mediated oxidation reactions can be effectively promoted by iron-containing zeolites, although structural information on the interaction between oxidant and metal centre is limited. Here, the authors report the characterization of the N 2 O-ligated Fe( ii ) active site in iron-exchanged zeolite beta.